A Congenital Deadly Association: Dilated Cardiomyopathy and Long QT Syndrome - Neiberg de Alcantara Lima; Antonio Thomaz de Andrade; Stela M V Sampaio; Mark Loehrke (Journal of Cardiac Arrhythmias, 2020)
Long QT syndrome is one of the most feared entities in hospitalized patients due to the potential risk for ventricular tachycardia and sudden death. Association between channelopathies and congenital cardiomyopathy is a new entity that has been studied recently. We report an interesting case of this association that maybe related to a genetic mutation.